Identification and quality control assessment of two herbal medicines by volatile oil analysis - Ibrahim Jantan,; Nurhayati Md Osman,; Bukhori Abu Bakar,; Abu Said Ahmad, (Penerbit UKM, 2003)
Analysis of volatile components by co-chromatography with authentic samples on two co,umns of different polarity, GC-MS and linear retention indices were applied to two herbal medicines of Air Mancur (Jamu Tujuh Angin and Jamu Nafsu Makan) as a rapid method for identification and quality assessment purposes. There was no compositional differences and little variation in the levels of each component between the oils of similar preparation obtained from three different locations. The oils obtained from the two herbal medicines were found to possess some compositional similarities, suggesting the use of mainly similar aromatic ingredients in the preparations. Both oils were rich in sesquiterpenoids where ar-curcumene (19.6 – 27.1%), b-curcumene (8.4 – 13.2%) and xanthorrhizol (7.0-9.9%) were the manor components. The presence of appreciable amounts of menthol (7.4 – 10.6%) and anethol (4.1 – 5.9%) in Jamu Tujuh angin and a higher concentration of thymol (9.6 – 11.4%) in Jamu Nafsu Makan may be used to differentiate the oils.